Fatty acid liposomes in cosmetic cream / Chia Si Wai - Chia, Si Wai (2014)

(untitled)
Liposomes have been used widely as carriers for active ingredients in cosmetic because of their ability to encapsulate both hydrophilic and hydrophobic compounds. In this work, fatty acid liposomes were prepared and introduced into olive oil-in-water emulsions stabilized by C14–C18 sucrose ester mixtures at pH 8.5. Light microscopy images of the emulsions showed evidence of the coexistence of oleic acid liposomes and the emulsion droplets. As alkyl chain length of sucrose ester increased, the average droplet size decreased, while the zeta potential became more negative. Further decrease of droplet size was observed when borate buffer was added to the aqueous phase. The free fatty acids in sucrose esters and olive oil are neutralized in borate buffer; consequently, fatty acid salts were produced and served as co-surfactants. The synergistic stabilization of emulsions by the mixture of sucrose esters and fatty acid salt resulted in higher stability, smaller droplet size, and lower polydispersity. The drastic increase in negative zeta potential was possibly due to the presence of free fatty acid salts in the emulsion systems. The flow curves at steady rate displayed five distinctive regions. The polydispersity of droplets enhanced the shear thickening effect at low shear rates and shear-banding effect at middle shear rates. Formation of fatty acid salts as co-surfactants caused the viscosities of the emulsions to increase by an order of magnitude. Similar changes can be seen in the G’ and G’’. The great enhancement of the G’ indicates the emulsion was too stiff and rigid. The presence of oleic acid liposome significantly reduced the viscosities and viscoelasticity of the emulsion by half an order of magnitude; this decreased viscosity and viscoelasticity helped enhance better spreadability.